Accumulation of potentially toxic elements in vegetable-cultivated soils from an agri-intensive region of southwest Punjab, India: contamination status and the effect of crop rotation - Sahoo, Prafulla Kumar; Barman, Harish Chandra; Kumar, Hemant; Ngangom, Lamnganbi; Chaudhari, Umakant (Frontiers in Soil Science, 2025)
Uranium (U) and other potentially toxic element (PTE) in cropland have become a major concern for food safety in the Malwa region of Punjab, India. However, limited information is available on the baseline status of these contaminants in vegetable-cultivated soil (CS) and their link to crop rotation patterns. To address this, a total of 149 CS samples (0–10 cm depth) were collected from different sites in the Bathinda and Mansa districts of Punjab during the winter season of 2023–2024. In other seasons, these sites are cultivated with either vegetables or other crops, such as rice, wheat, cotton, and maize, as part of a crop rotation system. Based on the sequence of previous and current crops in each site, the cultivated soils were categorized into different groups, with vegetable–vegetable (VG–VG) and rice–vegetable (RC–VG) rotations being the most dominant. Additionally, 12 undisturbed/uncultivated soil (US) samples were collected for comparative analysis and to estimate the region’s background PTE levels. The results showed that the soils were slightly alkaline (pH: 6.56 to 9.29; average, 7.9) and not saline (EC: 173 to 3,230 µS cm−1) in nature. The contents of U and PTEs were significantly higher (p < 0.05) in CS samples compared to US samples; however, when compared with the regional studies and the reference values of world and Indian soils, all concentrations remained within the limits, indicating no significant enrichment. The content of PTEs did not vary significantly between the two crop rotation patterns, although slightly higher levels of PTEs were noted for RC–VG group. The pollution indices (calculated using site-specific background values), such as contamination factor (CF) and enrichment factor (EF), revealed low to moderate level of contamination in CS samples, except Pb, which showed moderate to very high levels of pollution. Furthermore, the pollution load index (PLI; 0.7 to 2.8) and potential ecological risk (RI; 41 to 250) suggested a low to moderate risk category for PTEs with Cd and Pb being the major contributors. Fertilizer analysis revealed that this contamination may be attributed to the overuse of chemical fertilizers, especially phosphate-based fertilizers, which enriched with U, Cd, Pb, and other PTEs. Although U-enriched groundwater, in conjunction with phosphate fertilizers, could contribute to higher U content in cultivated soils, its impact on U accumulation in VG-cultivated lands appeared to be minimal. Principal component analysis (PCA) and the significant correlation (p < 0.01) between Fe-Mn and Zn-Cr-Cu-Ni-As-Cd-U suggest that secondary Fe/Mn oxyhydroxides play a major role in adsorbing these elements in soils. These findings provide baseline information on the PTE levels in vegetable-cultivated soils in the region, which can support the development of strategies for sustainable land management and improve crop quality in this region.